IDH-mutant astrocytomas with primitive neuronal component have a distinct methylation profile and a higher risk of leptomeningeal spread - Hinz, Felix; Friedel, Dennis; Korshunov, Andrey; Ippen, Franziska M.; Bogumil, Henri; Banan, Rouzbeh; Brandner, Sebastian; Hasselblatt, Martin; Boldt, Henning B.; Dirse, Vaidas; Dohmen, Hildegard; Aronica, Eleonora; et al. (Acta neuropathologica, 2025)
IDH-mutant astrocytomas are diffuse gliomas that are defined by characteristic mutations in IDH1 or IDH2 and do not have complete 1p/19q co-deletion. The established grading criteria include histological features of brisk mitotic activity (grade 3) and necrosis and/or microvascular proliferation (grade 4). In addition, homozygous deletion of the CDKN2A/B locus has recently been implemented as a molecular marker for grade 4 IDH-mutant astrocytomas. Here, we describe a subgroup of high-grade IDH-mutant astrocytomas characterised by a primitive neuronal component based on histology and a distinct DNA methylation profile (n = 51, ASTRO PNC). Misinterpretation as carcinoma metastasis was common, since GFAP expression was absent in the primitive neuronal component, whereas TTF-1 expression was detected in 15/19 cases (79%) based on immunohistochemistry. Apart from mutations in IDH1, TP53, and ATRX, we observed enrichment for alterations in RB1 (n = 19/51, 37%) and MYCN (n = 14/51, 27%). Homozygous CDKN2A/B deletion (n = 1/51, 2%) and CDK4 amplification (n = 3/51, 6%) were relatively rare events. Clinical (n = 31 patients) and survival data (n = 23 patients) indicate a clinical behaviour similar to other CNS WHO grade 4 IDH-mutant astrocytomas, however with an increased risk for leptomeningeal (n = 7) and extra-axial (n = 2) spread. Taken together, ASTRO PNC is defined by a distinct molecular and histological appearance that can mimic metastatic disease and typically follows an aggressive clinical course.
Gesehen am 30.09.2025